2012
DOI: 10.1016/j.janxdis.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of facial blood flow on ratings of blushing and negative affect during an embarrassing task: Preliminary findings

Abstract: Expecting to blush is a common source of social anxiety, and is associated with heightened perceptions of blushing and embarrassment. To assess whether sensory cues associated with heightened facial blood flow are an additional source of anxiety, the vasodilator niacin (100 mg) or placebo was administered double-blind to 33 participants, and facial blood flow was investigated when they sang a children's song. Vasodilatation during singing was greater in the niacin than placebo condition, and niacin-evoked flus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…A few studies that used measures of physiological blushing (Drummond et al., ; Mulkens, de Jong, & Bögels, ) failed to find the relationship between physiological parameters of blushing and social anxiety. In contrast, other studies (Bögels, Rijsemus, & De Jong, ; Drummond & Lazaroo, ) supported the hypothesis that physiological blushing is related to social anxiety.…”
Section: Phenomenology Of Blushingmentioning
confidence: 79%
“…A few studies that used measures of physiological blushing (Drummond et al., ; Mulkens, de Jong, & Bögels, ) failed to find the relationship between physiological parameters of blushing and social anxiety. In contrast, other studies (Bögels, Rijsemus, & De Jong, ; Drummond & Lazaroo, ) supported the hypothesis that physiological blushing is related to social anxiety.…”
Section: Phenomenology Of Blushingmentioning
confidence: 79%
“…Human cardiovascular activities are important biological signals. They are convenient and reliable indicators of a variety of physiological and psychological activities and thus are widely used in human neuroscience research 1 3 . For example, during rest, cardiovascular activity is at the baseline level.…”
Section: Introductionmentioning
confidence: 99%
“…They also suggest that cumulative or exercise-induced increases in facial blood flow delay the resolution of flushing in people with a fear of blushing. Prostaglandins might contribute, in part, to this delay (Drummond and Lazaroo, 2012a;2012b) because cheek blood flow remained higher at the control than ibuprofen-treated site after exercise in the high-fear group.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found that a low dose of the vasodilator nicotinic acid (niacin) provoked greater increases in facial blood flow in people with high than low fear of negative evaluation (a cardinal feature of social anxiety), both when they sat quietly (Drummond and Lazaroo, 2012a) and during an embarrassing task (singing a children's song) (Drummond and Lazaroo, 2012b). Niacin dilates superficial blood vessels by releasing prostaglandin D 2 from epidermal Langerhans cells and prostaglandin E 2 from keratinocytes (Benyo et al, 2006;Hanson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation